Efficiency of Crop–Livestock Production Systems Under Conservation Agriculture: Scope for sustainable system transformation to Achieving Food Security in Rain-Fed Drylands of Tunisia - Dhehibi, Boubaker; Souissi, Asma; Fouzai, Ayoub; Frija, Aymen; Abdeladhim, Mohamed Arbi; Rekik, Mourad (International Center for Agricultural Research in the Dry Areas, 2023)
The objective of this study is to evaluate the technical efficiency of farmers engaged in mixed crop–livestock systems under conservation agriculture (CLCA) in Tunisian rainfed areas who are using Resource-Conserving Technologies (RCTs) such as forage mixture, minimum and zero tillage, and small machinery.